Answer to Question #2746 in Calculus for stuff

Question #2746
‎6[sup]x-1[/sup] =3[sup]2x[/sup]
Expert's answer
3(x-1)* 2(x-1) = 32x
2(x-1)= 3(2x-x+1)
2(x-1)= 3(x+1)
2(x-1)= 9*3(x-1)
(2/3)(x-1)= 9
x-1 =log(2/3)9
x=1+log(2/3)9=log(2/3)2/3* 9=log(2/3)6

Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be first!

Leave a comment

Ask Your question

LATEST TUTORIALS
New on Blog
APPROVED BY CLIENTS
paypal